Seven Lamps of Architectural Design - Bruno Gil (Joelho)
In the present, the contemporary model of the Design and Design Studio is constantly being tested and revised, before a rising heterodoxy of programs and methods. As a key, it is proposed the retrieval of John Ruskin’s essay “Seven Lamps of Architecture”. Written in 1849, the seven principles aimed to rescue, in an almost primitive way, Architecture as an Art that enlightens the remaining ones.  It returns to the example of Venice’s medieval stones to go forward on the symbolic indefiniteness of the industrial age, alerted by Pugin (1836). Ruskin’s lamps would indicate the modern way for the “total artwork” by William Morris. With Morris, the Design would be a part of a single process from concept to work, anticipating Bauhaus’s Modern Design - the “gesamtkunstwerk”.